2016
DOI: 10.3174/ajnr.a4917
|View full text |Cite
|
Sign up to set email alerts
|

Preradiotherapy MR Imaging: A Prospective Pilot Study of the Usefulness of Performing an MR Examination Shortly before Radiation Therapy in Patients with Glioblastoma

Abstract: BACKGROUND AND PURPOSE:Current protocols in patients with glioblastoma include performing an MR examination shortly after surgery and then 2-6 weeks after ending concomitant chemoradiotherapy. The assessment of this first postradiotherapy examination is challenging because the pseudoprogression phenomenon may appear. The aim of this study was to explore if performing an MR examination shortly before radiation therapy (preradiotherapy MR imaging) could improve the radiologic assessment of patients with glioblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…After considering these points, we found that the overall incidence that we observed (48%) is similar to that reported in a few other studies with smaller sample sizes [1214]. The clinical impact of this early tumor growth is reflected in the significantly shortened PFS and OS seen in patients who developed early tumor growth.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…After considering these points, we found that the overall incidence that we observed (48%) is similar to that reported in a few other studies with smaller sample sizes [1214]. The clinical impact of this early tumor growth is reflected in the significantly shortened PFS and OS seen in patients who developed early tumor growth.…”
Section: Discussionsupporting
confidence: 88%
“…Radiotherapy treatment volumes are defined by a planning CT and comparison to immediate postoperative MRI. A few small studies of glioblastoma patients enrolled in clinical trials that included pre-radiotherapy MRI have investigated the phenomenon of early tumor growth, as evidenced by increased contrast-enhancement in the interval between surgery and the initiation of radiation [1214]. Results of these studies show that a certain proportion of patients have new or increased enhancement suggesting progressive disease.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of all glioblastoma patients develop macroscopically observed REP between surgery and postoperative radiotherapy, which is associated with a shorter survival (Table 1 and Fig. 1A) [5][6][7][8][9][10][11][12][13]. From a biological perspective, macroscopically observed REP is associated with extent of resection and volume of residual Fig.…”
Section: Rapid Early Progressionmentioning
confidence: 98%
“…In the time between surgery and radiotherapy, remnant tumour cells remain untreated causing rapid early progression (REP), which is associated with a shorter survival [5][6][7][8][9][10][11][12][13]. This highlights the limitations of the current glioblastoma treatment pathway and the desperate need for new strategies.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that PRMRI could provide a more accurate baseline for subsequent imaging studies compared to EPMRI, due to the detection of any interval changes occurring between EPMRI and the initiation of chemoradiotherapy [57]. These changes include tumour growth [57][58][59] and new reactive non-neoplastic enhancement [11,52,53], both of which can confound treatment response assessment on subsequent imaging studies. Pseudoprogression and radiation necrosis are two welldocumented forms of PTRE.…”
Section: Comparison With Other Studies and Study Relevancementioning
confidence: 99%